Knowledge, attitudes and practices of adult patients seen in ENT consultation facing COVID-19 in Lomé, Togo - Winga Foma; Essobozou Pegbessou; Warou Dolou; Aboudourazak Amadou; Stephen Lionel Antoine Lawson; Bathokedeou Amana; Essohanam Boko; Eyawèlohn Kpemissi (Journal of Interventional Epidemiology and Public Health)
Introduction: The objective of this study was to verify the knowledge, attitudes and practices of patients received in an ENT consultation in Lom´ in the face of COVID-19 in order to better guide information, education and communication campaigns.